2021
DOI: 10.1002/iid3.504
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low‐level pretransplant donor‐specific antibodies on outcomes after kidney transplantation

Abstract: Background: The effect of low-level pretransplant donor-specific antibody (DSA) on kidney transplant outcomes is not well described. The goal of this study was to compare outcomes among patients of varying immunologic risk, based on the level of pretransplant DSA. Methods:We retrospectively reviewed all adult kidney transplant recipients who had undergone a transplant at our center between January 2013 and May 2017. Patients were grouped as negative DSA (mean fluorescence intensity, [MFI SUM < 100]), low-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The association of preformed HLA-DSAs with poor kidney allograft outcomes has been long established in the literature. Recent large and international cohort studies (with n = 3237–4724 patients) have confirmed and validated this well described association across multiple settings including deceased donor transplantation, analyses of recipient pairs receiving a kidney from the same donor and living donor transplantation [17 ▪ ,18,19]. In addition, other studies (with n = 174–924 patients) have confirmed that performed HLA-DSAs with MFI> 3000 were associated with decreased kidney allograft survival [20 ▪▪ ,21].…”
Section: Human Leukocyte Antigen-donor-specific Antibodies For Immune...mentioning
confidence: 72%
“…The association of preformed HLA-DSAs with poor kidney allograft outcomes has been long established in the literature. Recent large and international cohort studies (with n = 3237–4724 patients) have confirmed and validated this well described association across multiple settings including deceased donor transplantation, analyses of recipient pairs receiving a kidney from the same donor and living donor transplantation [17 ▪ ,18,19]. In addition, other studies (with n = 174–924 patients) have confirmed that performed HLA-DSAs with MFI> 3000 were associated with decreased kidney allograft survival [20 ▪▪ ,21].…”
Section: Human Leukocyte Antigen-donor-specific Antibodies For Immune...mentioning
confidence: 72%
“…Thammanichanond and colleagues (Thammanichanond et al, 2012) showed that recipients with a negative CDCXM but positive DSA detected by Luminex™ had a higher incidence of AMR but with no statistically significant impact on delayed graft function, patient survival or 1-and 5-year graft survival, when compared with DSA negative patients. Similarly, (Parajuli, Bath, et al, 2021) did not see any effect of DSA on graft or patient survival. In con- • Whether the donor is homozygous at a given loci (and MFI level of DSA doubled) • Presence of supertypic antibodies such as Bw4…”
Section: Pre-transplant Testing Recommendationsmentioning
confidence: 83%
“…The MFI level does not sufficiently predict long‐term graft outcome due to well‐known limitations of the SAB assay (prozone effect, bead saturation, shared epitope phenomenon, etc.) 10,11 . In addition, it has been suggested that especially complement binding DSAs are pathogenic.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The MFI level does not sufficiently predict long-term graft outcome due to wellknown limitations of the SAB assay (prozone effect, bead saturation, shared epitope phenomenon, etc.). 10,11 In addition, it has been suggested that especially complement binding DSAs are pathogenic. Although biopsies of rejected grafts showed positive C4d deposition, [12][13][14] convincing evidence has emerged that antibody-mediated rejection could also occur in absence of positive C4d staining.…”
Section: Introductionmentioning
confidence: 99%